Lead-free ferroelectric materials: Prospective applications - Zhang, Shujun; Malič, Barbara; Li, Jing-Feng; Rödel, Jürgen (Journal of materials research, 2021)
The year of 2021 is the 100th anniversary of the first publication of ferroelectric behaviour in Rochelle salt, focussing on its piezoelectric properties. Over the past many decades, people witnessed a great impact of ferroelectricity on our everyday life, where numerous ferroelectric materials have been designed and developed to enable the advancement of diverse applications. Now the driving forces for ferroelectric studies stem from regulations on environment, human health and sustainable society development. This leads to the resurgence of lead-free ferroelectric materials for the expectation of replacing the state-of-the-art lead-based counterparts. The next wave of explorations into ferroelectric materials maybe related to the Internet-of-Things, which requires millions of self-powered sensors and memories. This will promote research on ferroelectrics for sensing, energy harvesting and storage, communication and non-volatile memories, from centimetre scale to micro and nanoscale. This review gives a brief discussion from the materials viewpoint, on the challenges and current status of lead-free ferroelectrics based on prospective applications. Graphic Abstract